Influence of Pb(II) in the sorption of As(V) by a Ca-polygalacturonate network, a root mucilage model. Issue 3 (4th May 2019) - Garau, Giovanni; Diquattro, Stefania; Lauro, Gian Paolo; Deiana, Salvatore; Castaldi, Paola
ABSTRACT: In this study, the role of lead [Pb(II)] in the sorption of arsenate [As(V)] by a Ca-polygalacturonate network (CaPGA), i.e. a model of root mucilage, was determined in acidic conditions (pH 4.5) commonly occurring at the soil–root interface. Sorption isotherms and kinetics showed that CaPGA was able to sorb As(V) ( 0.89 mmol g −1 CaPGA) only in the presence of Pb(II). The concurrent sorption of Pb(II) by CaPGA ( 2.30 mmol g −1 ), and the FT-IR spectra, suggested the formation of binuclear complexes involving one As(V) anion and two Pb(II) cations, which were in turn involved in bridging complexes with two carboxylate groups of CaPGA. The As(V) sorption by the Pb(II)-PGA system followed a pseudo-second-order kinetic model, while the sorption isotherms data fitted the Langmuir model better than the Freundlich one. The release of As(V) and Pb(II) from the As(V)-Pb(II)-PGA system, following treatment with environmentally relevant organic acids, i.e. citric and malic acids (0.0–24 mM concentration range), showed that As(V) was strongly retained and that both organic acids were able to mobilize similar As(V) and Pb(II) pools. Plant growth experiments showed that CaPGA was effective at reducing the As(V) phytotoxicity toward triticale plants (× Triticosecale Wittm.) in the presence of Pb(II), highlighting the environmental relevance of the interactions reported in this study.